Mapping an Internal-Eksternal Matrix Sentra Getuk Pisang Based On McKinsey’s 7S Framework and PEST - Winahyu, Yosi Try; Marlena, Novi (Universitas Muhammadiyah Magelang, 2021)
Getuk pisang is one of traditional snack in Kediri. Sentra Getuk Pisang Dusun Jatisari, which is the main supplier of getuk pisang in Kediri, had decline sales caused by pandemic. The purpose of this study is 1) Analyze the internal and external conditions of Sentra Getuk Pisang Dusun Jatisari, 2) Analyze the position of Sentra Getuk Pisang Dusun Jatisari using the Internal-External (IE) matrix and 3) Provide recommendations strategies that can be applied to the Sentra Getuk Pisang Dusun Jatisari. This study used non-probability sampling with interactive analytical techniques from Miles and Huberman consist with data collection, data reduction, data display and conclusion: drawing/verifying. The results showed that the IFE matrix was 2.43, EFE 2.8 and the IE matrix was in quadrant V or hold and maintain. Recommended strategy that can be used at Sentra Getuk Pisang Dusun Jatisari is market penetration by utilizing online media and product development.